2017
DOI: 10.4311/2015mb0133
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of polyethylene by bacterial strains isolated from Kashmir Cave, Buner, Pakistan

Abstract: Low density polyethylene (LDPE) is used for making common shopping bags and plastic sheets and is a significant source of environmental pollution. The present study was aimed at testing the ability of bacterial strains identified as Serratia sp. KC1-MRL, Bacillus licheniformis KC2-MRL, Bacillus sp. KC3-MRL and Stenotrophomonas sp. KC4-MRL isolated from a limestone cave to degrade polyethylene. These strains were isolated from soil of Kashmir Smast, a limestone cave in Buner, Pakistan. These strains showed anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Some of these compounds can be very toxic, but can be transformed into less toxic compounds by various biological pathways [81, 82]. It has been reported that stress or low nutrient habitats can force living microoganisms to use any available nutrients to survive [83]; thus, cave-dwelling microroganisms may use the by-products of xenobiotic biodegradation for energy, nutrients, or final electron acceptors for their growth [79]. For instance, it has been reported that various bacteria ( Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds can be very toxic, but can be transformed into less toxic compounds by various biological pathways [81, 82]. It has been reported that stress or low nutrient habitats can force living microoganisms to use any available nutrients to survive [83]; thus, cave-dwelling microroganisms may use the by-products of xenobiotic biodegradation for energy, nutrients, or final electron acceptors for their growth [79]. For instance, it has been reported that various bacteria ( Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…KC3-MRL, Stenotrophomonas sp. KC4-MRL) isolated from soil samples of Kashmir Smast, a limestone cave in Khyber Pakhtoonkhuwa province, Pakistan, are capable of degrading polyethylene [83]. Therefore, it is also likely that xenobiotic biodegradation and metabolism might be another important process in sustaining diverse groups of microorganisms in Manao-Pee cave.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study (Fig. 8 ), the characteristic peak at 2915 cm - 1 , 2928 cm −1 , and 2848 cm −1 indicate the asymmetric and symmetric C-H stretching vibration respectively [ 38 ]. The band at 1470 cm −1 [ 39 ] became remarkably weaker after microbial treatment providing the evidence of the presence of the C = H bond.…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, Jamil et al (49), reported that Serratia sp. KCI-MRL, Bacillus licheniformis KC2-MRL, Bacillus sp.…”
Section: Plastics Degrading Bacteriamentioning
confidence: 99%
“…KC4-MRL isolated from the soil in Khasmir Smast, Pakistan, were able to damage the surface of LDPE plastic films within one month of incubation. Harshvardhan and Jha, cited from Jamil et al (49) stated that LDPE biodegradation through a series of enzymatic reactions involving various enzymes that catalyze chemical changes of plastic polymers such as oxidation, reduction, hydrolysis, esterification, and molecular inner conversion.…”
Section: Plastics Degrading Bacteriamentioning
confidence: 99%